Honey Encryption : implementation challenges and solutions - Lindholm, Ronja (2019)
Most encryption techniques have one essential problem: they are vulnerable to brute-force attacks. In 2014, a new defence mechanism was introduced against brute-force attack and this mechanism was called Honey Encryption. Honey Encryption has been cited in several articles and it has demonstrated potential to be an additional security method alongside conventional encryption. This thesis will offer an overview of the current situation of Honey Encryption and it starts by explaining and discussing the challenges that have been brought up. These challenges include, among other things, the difficulty of producing the honey messages and identifying user typos from an attack. Some of the solution ideas that have been introduced since the introduction of Honey Encryption are discussed as well. There have been some new types of data that could be used with Honey Encryption, such as genomes and multi-dimensional data such as images and videos. These data types are discussed in connection with the use of Honey Encryption. As a last measure to provide overall understanding of the current situation of HE, this thesis provides an implementation model for Honey Encryption in a theoretical level, with some practical programming parts as well. The model is offered by going through the Honey Encryption scheme step by step. Together, these three steps: challenges, new data types, and an implementation model are meant to give a broad view of the situation of Honey Encryption gathered in one place.